Highway Safety Factor - Arismawan Arismawan (Industrial Engineering Journal, 2016)
Road safety is an important aspect of the targeted improvement of highway transportation system in addition to the smoothness, safety, reliability, efficiency and harmony with the environment. Traffic safety indicator is the main component result in whether high or low levels of traffic accidents. Traffic safety is constantly becoming increasingly urgent needs to be realized in the implementation of national transport policy. No exaggeration when safety in road is included as one indicators of public welfare as a sign of success or failure in the development of infrastructure.